Clinical significance of pretreatment metabolic tumor volume and total lesion glycolysis in hypopharyngeal squamous cell carcinomas. Issue 7 (2nd August 2014) - Roh, Jong‐Lyel; Kim, Jae Seung; Kang, Byung Chul; Cho, Kyung‐Ja; Lee, Sang‐wook; Kim, Sung‐Bae; Choi, Seung‐Ho; Nam, Soon Yuhl; Kim, Sang Yoon
ABSTRACT Background To evaluate the usefulness of metabolic tumor volume (MTV) and total lesion glycolysis (TLG) measured by pretreatment fluorine 18‐fluorodeoxyglucose (18F‐FDG) positron emission tomography (PET)/computed tomography (CT) as predictors of clinical outcome in hypopharyngeal squamous cell carcinoma (HPSCC). Methods Seventy‐eight patients with HPSCC treated with definitive radiotherapy with or without chemotherapy underwent 18F‐FDG PET/CT. Maximum standardized uptake value (SUVmax), MTV, and TLG were measured. For calculation of MTV, 3‐D regions of interest were drawn and a SUV threshold of 2.5 was used for defining region. Univariate and multivariate analyses identified variables associated with disease‐free survival (DFS) and overall survival (OS). Results Median SUVmax, MTV, and TLG were 9.0 (range, 1.7–24.5), 20.5 (0.3–339.9) ml, and 98.9 (0.8–1877.1) g, respectively. The four‐year DFS and OS were 56.1% and 52.6%, respectively. On univariate and multivariate analyses, MTV (P = 0.014) and TLG (P = 0.029) were independent prognostic factors for DFS, and MTV (P = 0.002) and TLG (P = 0.002) were independent prognostic factors for OS. Conclusion MTV and TLG measured by pretreatment 18F‐FDG PET/CT may be useful in predicting the clinical outcomes of HPSCC patients undergoing radiotherapy. J. Surg. Oncol. 2014 110:869–875. © 2014 Wiley Periodicals, Inc.